Partisipasi Warga dan Pemberdayaan Ekonomi melalui Bank Sampah Induk di Kota Semarang - Eka Puji Srilestari (Jurnal Riptek, 2025)
This study examines the dual role of the Main Waste Bank (Bank Sampah Induk) in Semarang City as a driver of community participation and economic empowerment. Using a qualitative-descriptive approach, data were collected through in-depth interviews, field observations, and document analysis involving waste bank managers, community members, and local government representatives. The findings reveal that citizen participation is primarily motivated by economic incentives (62% of respondents) and environmental awareness (38%), though challenges such as lack of outreach and time constraints persist. Economically, the waste bank contributes an additional monthly income of IDR 150,000–500,000 per member through waste sales and recycled product businesses, yet its sustainability is hindered by fluctuating recyclable market prices and limited infrastructure. Institutional support, such as local regulations (Perda No. 5/2019) and partnerships with recycling industries, emerges as a key enabling factor. The study highlights the potential of waste banks as a circular economy model but underscores the need for improved digital integration, capacity-building programs, and multi-stakeholder collaboration to ensure long-term impact. These findings contribute to broader discussions on community-based waste management and inclusive urban development in Indonesia.